I2PL—What is it and what does it mean?. Issue 2 (17th February 2021) - Bjerring, Peter; Petersen, Steffen B.; Mosegaard, Mille L.
Abstract: Intense pulsed light (IPL) is today a standard tool in most cosmetic and dermatological clinics providing a variety of optical treatment options. The range of available IPL systems keeps growing and today's physicians have a wide selection to choose from. IPL can be separated into broadband IPL and narrowband IPL. Broadband IPL heats the ubiquitous tissue water in the skin leading to unspecific heating of the tissue and increasing risk of side effects. To reduce this, contact cooling is needed, which can negatively influence treatment efficiency. Narrowband IPL limits the spectra of emitted light, thus reducing the energy reaching the skin. Square‐shaped pulses provide the best light output characteristics and square pulses are obtained with large electrical capacitor banks and advanced pulse shutter mechanisms. Longer wavelengths reaching the skin surface lead to absorption in tissue water and doubles energy requirements as compared to systems filtering away wavelengths above 950 nm, known as narrowband I 2 PL. Having a long wave cut‐off filter at 950 nm halves the energy requirement and reduces the risk of side effects. It also eliminates the need for active cooling of the surplus energy and thus enhances treatment results and comfort. Ideally, systems should be able to provide pulses with a duration shorter than 1 ms with sufficient energy to create purpura if needed. Individual adjustment of pulse duration and fluency provides for more efficient treatments and allows treating a wider variety of patients. Systems allowing parameters to be adjusted based on "patient parameters" reduces the risk that improper settings are used.